Employee Wellbeing and Work Productivity: The Role of Psychological Capital - Siti Nur Azizah; Yang Xiang; Zhou Hui (Yayasan Adra Karima Hubbi, 2025)
In the contemporary workplace, employee wellbeing has emerged as a critical factor influencing work productivity. Psychological capital (PsyCap), encompassing hope, efficacy, resilience, and optimism, is posited as a key driver in enhancing both wellbeing and productivity. Despite its potential, the role of PsyCap in mediating the relationship between employee wellbeing and productivity remains underexplored. This study aims to investigate the role of psychological capital in linking employee wellbeing to work productivity, providing insights into how organizations can leverage PsyCap to foster a productive workforce. A quantitative approach was employed, utilizing structured surveys distributed to 350 employees across various industries. Data were analyzed using structural equation modeling (SEM) to examine the mediating role of PsyCap. The findings reveal that psychological capital significantly mediates the relationship between employee wellbeing and work productivity. Employees with higher levels of PsyCap reported greater wellbeing and demonstrated enhanced productivity. Hope and resilience emerged as the most influential components of PsyCap in this context. This study underscores the importance of psychological capital as a pivotal mechanism connecting employee wellbeing to productivity. Organizations are encouraged to invest in PsyCap development programs to cultivate a resilient and optimistic workforce, ultimately driving organizational success.